Sifat Mekanis pada Kompon Karet Alam Variasi Campuran Serbuk Ban Bekas untuk Aplikasi Bantalan Mesin - Agus Suharto; Joko Sedyono (Creative Research in Engineering, 2021)
Rubber is a good material used for engine mounting because it has good elastic and damping properties. To obtain good mechanical and damping properties, fillers can be added such as carbon black, nylon powder and silica. In this study used used tire crumb as filler material. With the method of adding used tire powder 0 phr, 6 phr, 12 phr, 18 phr sequentially on natural rubber compound A, B, C, and D. Rubber compounds made in this process are tested to determine the mechanical properties and Dumping vibrations. Tests carried out namely, strength and elongation at break, hardness, tearing strength, flex crack resistance and dumping vibration ( ability to reduce acceleration of vibration propagation ). The test results show a decrease in the strength of 21.7 N / mm², 20.9 N / mm², 20.3N / mm², 20.5 N / mm², and also at the elongation at break test with an average of 430%, 415%, 423%, 425%. Sequentially on A, B, C and D vulcanizates. Trends of hardness test chart to increase  61 Shore A, 63 Shore A, 64 Shore A and 65 Shore A, while the tear strength also shows an increase and decrease with an average yield of 12.5 N / mm², 12.6 N / mm², 11.3 N / mm², 13.3 N / mm² on  A, B, C and D vulcanizates.